Fostering global talent among students in Universiti Teknologi Malaysia via Study Abroad Programme - Fasihah Mohd Jaslan; Mohd Ariffin Abu Hassan; Nur Izzati Adnan; Nor Haniza Sarmin (Penerbit Universiti Kebangsaan Malaysia, 2020)
Universiti Teknologi Malaysia (UTM) is continuing its quest to become the nation’s top educational institution which is translated in one of the six Key Focus Areas (KFAs) in UTM Global Plan 2020 namely Global Prominence and Branding. As a one of the leading research universities in Malaysia, UTM also plays an important roles to produce a top-notch talent, attracting, developing and retaining high skilled individuals to propel into the future. Study Abroad Programme via UTM Outbound Mobility Program is one of the tools to produce global talent among students in UTM. This programme plays a crucial roles in ensuring UTM becoming one of the internationalized university in Asian region in achieving Malaysia Higher Education agenda to become an Education Hub in 2025. This study abroad programme comprises of both inbound and outbound. For UTM Outbound Mobility program, it is comprises of short term program and long term program including Global Outreach Program (GOP), International Invitation Program (conference, seminar, competition etc.) (IIP), Summer School Abroad (SSA), Research Internship Abroad (RIA) and Student Exchange Program (SEA). One of the initiatives is by encouraging at least ten percent of the total number of UTM students to experience cultural immersion via global education agenda by going abroad. This initiative will give value added elements to the students’ lifelong learning.